Pengaruh Kepatuhan Perawat Melakukan Hand Hygiene Terhadap Prevalensi Virus Hepatitis C Pasien Positif Di Ruang Hemodialisis - Isranil Laily, Eka (JINTAN: Jurnal Ilmu Keperawatan, 2025)
The risk factor for transmission of hepatitis infection through hemodialysis is estimated to be around 10% per year. Various studies have generally concluded that hepatitis C virus infection in hemodialysis patients is associated with nosocomial infections, the causative factor of infection is mainly due to the lack of sterilization techniques and cleanliness in dialysis equipment. Based on this, the researcher is interested in obtaining information about “The effect of nurse compliance in performing hand hygiene on the prevalence of positive Hepatitis C in the UPT Hemodialysis room at Deli Serdang Hospital.” This study uses the Quasi Experimental method using Time Series Design. The results showed that there was no significant influence between nurse compliance in performing hand hygiene with the prevalence of positive Hepatitis C in the Hemodialysis room based on the chi square test with a p value of 0.218> 0.05. Hospitals should make efforts to increase standard vigilance related to infection prevention and control, especially transmission of the hepatitis C virus in hemodialysis patients and for further researchers it is hoped that they will develop research in conducting research related to increasing the prevalence of Hepatitis C.